Heart rate responses to small-sided games among elite junior rugby league players - Foster, C. D; Twist, C.; Lamb, K. L.; Nicholas, C. W. (The Journal of Strength and Conditioning Research, 2010)
This study investigated the influences of player number and playing area size on the heart rate (HR) responses elicited by junior male rugby league players during small-sided games (SSGs). Twenty-two players from a professional club (n = 22, mean age: 14.5 +/- 1.5 years; stature: 172.5 +/- 11.4 cm; body mass: 67.8 +/- 15.1 kg; VO2peak: 53.3 +/- 5.6 mL/kg.min; HRmax: 198 +/- 7.8 beats/min) participated in 2 repeated trials of six 4-minute conditioned SSGs over a 2-week period. The SSGs varied by playing area size-15 x 25 m, 20 x 30 m, and 25 x 35 m-and player number-4v4 and 6v6. HRs were recorded continuously in each game and expressed as overall and age-related (15-16 and 12-13 years) means and percent of maximum (%HRmax). Analysis revealed nonsignificant (p > 0.05) effects of trials and playing area size on HRs but a significant effect of player number in the 15-16 age group only (p < 0.001), with HRs being higher in the 4v4 (90.6% HRmax) than the 6v6 SSGs (86.2% HRmax). The HR responses were found to be repeatable in all SSG conditions (within +/- 1.9% HRmax), apart from the small 6v6 condition in the older players. The findings demonstrate that these SSGs generate physiological responses suitable for aerobic conditioning that, although unaffected by the size of the area used, are sensitive to the player number. Accordingly, among such players it is advisable that coaches use 4v4 SSGs to achieve an appropriate and consistent aerobic conditioning stimulus.